A Comprehensive Review of Teneligliptin on its Pharmacological, Pharmaceutical, and Analytical Profile - Krishna, Pusuluri Siva (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Teneligliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor that has gained prominence in the management of type 2 diabetes mellitus (T2DM). Pharmacologically, teneligliptin acts by inhibiting DPP-4, prolonging the action of incretin hormones, and promoting insulin secretion while reducing glucagon release. Clinical studies have established its efficacy in improving glycaemic control with a favorable safety profile. Pharmaceutically, teneligliptin is available in various dosage forms, including tablets and combination therapies, offering flexibility in treatment regimens. Its rapid absorption and relatively short half-life contribute to convenient dosing and patient adherence. Analytically, rigorous methods are employed to assess teneligliptin’s purity, stability, and bioavailability, ensuring consistent and reliable dosing. Its pharmacological efficacy, diverse pharmaceutical formulations, and rigorous analytical assessment collectively make it a valuable option in the therapeutic armamentarium for managing T2DM. Staying informed about the latest developments in teneligliptin research is essential for optimizing its clinical use.